Pharmacokinetics of dimeric dipeptide mimetic of nerve growth factor GK-2 in rats. Part 2. Kinetics of distribution in organs and tissues - G. B. Kolyvanov; A. A. Litvin; P. O. Bochkov; O. Yu. Kravtsova; O. G. Gribakina; P. Yu. Povarnina; V. P. Zherdev (LLC "Publisher OKI", 2024)
Relevance. To introduce the GK-2 compound into clinical practice, it is necessary to conduct a preclinical study of its pharmacokinetics, in particular, the distribution of the studied drug in organs and tissues. The aim is to study the tissue availability of a new original compound GK-2 in rats after its intraperitoneal administration. Methods. Quantitative determination of GK-2 in blood plasma and organ/tissue homogenates of rats was carried out by high-performance liquid chromatography with mass spectrometric detection. Results. The distribution of GK-2 in organs and tissues with varying degrees of vascularization was studied in rats. It was found that after a single intraperitoneal injection of GK-2 at a dose of 150 mg/kg, the studied compound was recorded in blood plasma for 2 hours, its half-life (t1/2el) was 0.4 hours. In organs and tissues, GK-2 was detected from 1.5 to 2 hours. The tissue availability of GK-2 in the liver - blood plasma system was 18.68; "kidneys - blood plasma" - 1.26; "spleen - blood plasma" - 0.68; "skeletal muscles - blood plasma" - 0.31. For the target organ, the brain, the tissue availability was 0.24. In the brain, the time to reach the maximum concentration of GK-2 (0.77 mcg/g) was 0.34 hours. It was found that GK-2 is excreted more slowly from the brain (t1/2el was 0.75 h) than from other organs and tissues (from 0.31 h for the spleen and up to 0.47 h for the kidneys).